Aerofracturelastic on wing box of multi-purpose commuter aircraft under gust lby means of XFEM - Abdullah, Nur Azam; Wirawan, Nanda; Curiel-Sosa, J.L.; Akbar, Mahesa (2018)
In this paper, crack behavior of an aluminum wing box under gust load is presented. The investigated wing box is based on one of the design prototypes of a multi-purpose commuter aircraft. The wing box has been tested experimentally for the vibration test and flutter test. The results of both tests are applied to verify the FEM model used in the present work. The detailed 3D FEM result is in good comparison with the experimental results. Several gust responses are plotted with the incremental of time to observe the deflection of the wing box. As the deflection under gust load resulting in developing the stress concentration at any discontinuity point, the crack has been initiated. By implementing XFEM, the crack propagations have been modelled based on the fracture toughness of the wing box material.